Retaining the Mother Tongue while Learning Host Country’s Languages. A Study with Second Generation Sudanese Immigrant Children - Mohammed, Abdulghani Eissa Tour (International Journal of Language and Literary Studies, 2022)
Sadly, the destination of some vital national languages has been buried with their speakers during the whole death trips by land and sea, with the topic of migration affecting a lot of international and local news stations. The present study investigates the difficulties confronting Sudanese immigrant children when communicating in some indigenous languages besides learning the host countries’ languages. Most participants in the current study are multilingual Sudanese immigrants from areas and intense conflict zones such as Darfur, Blue Nile, and South Kordofan. The real issue is how immigrants who make it to their intended destinations preserve their home tongues and cultural traditions as sources of identity. The researcher employed a qualitative research methodology to carry out this investigation. An initial 58 Sudanese immigrants were interviewed. The study found that (1) it might be challenging to communicate with kids even though parents speak these languages at home. (2) this situation may decrease the number of those who speak these national languages and will result in losing the national identity of future generations in the diaspora unless this situation changes, (3) children of Sudanese immigrants in the diaspora learn primarily the host country language, in addition to their indigenous languages based on the data collection and analysis. It is recommended that parents should use their local language continually at home with their children to preserve their identity and cultural heritage.